PENINGKATAN KUALITAS SDM SERTA PENGEMBANGAN PRODUK DAN PENERAPAN TEKNOLOGI PADA KOPERASI PRODUKSI DI PROVINSI BANTEN - Muljadi, Muljadi; Syamsudin, Syamsudin (Community Services and Social Work Bulletin, 2021)
This community service seeks to improve the human resources (HR) of SMEs in Banten. The method will be qualitative descriptive. The researcher or informant will be the management or manager of five production cooperatives in Banten Province. An interactive model was utilized to analyze the data. This analysis paradigm has three components: data reduction, data display, and conclusion drafting. 1. This study found that conventional or manual administration of employees, unsophisticated financial management, and short-term marketing are still common in production cooperatives. Cooperative administrators or managers provide the sole training because they are MSME actors who have their own expertise. 2. To improve the goods of production cooperatives, comprehensive product development planning is required. Product development can help cooperatives survive by attracting new customers and increasing earnings. 3. Technology should be a major factor in cooperative product development, but Banten cooperatives have not effectively harnessed it. This cooperative has a lot of promise. The management of production cooperatives must be willing to focus more on product development and use technology that can speed up product creation for broad public demands. Local raw materials are a particular benefit for production cooperatives. However, the required working capital is low, allowing those with an entrepreneurial drive to start up business units with low technological sophistication